(untitled) (Bangladesh Journal of Medical Education, 2023)
Introduction: Academic performance of learners is challenging as MBBS students’ performance is a result of socio-economic, psychological and environmental factors. Socially secured education systems are growing as a profitable industry with prime goal to produce high quality education which delivers well-educated and skillful students, because institutions are valueless without quality of students. Objective: This study was carried out to find out students’ views on social security system for them in conveniently selected medical colleges of Bangladesh. Methods: This descriptive type of cross-sectional study was carried out at four medical colleges over a period of one year from January 2021 to December 2021. Convenience sampling technique was adopted to select the medical colleges. A self administered pretested questionnaire was used to collect data from 200 purposively selected students who were present in the lecture or online classes on the day of data collection. The security factors were divided into: External Security Factors (Extracurricular activities, family & academic life problems, work and financial, social and environmental other problems, problem-solving skills) and Internal Security Factors (Students’ competence & aptitude, academic life, environmental security measurement, physical or mental expectation, learning barriers and modern technology threats). Results: Among the total 200 students 116 (58%) were male and 84 (42%) were female. Maximum (i.e. 95%) of students expect better social security both internal and external factor. Moreover the maximum students expressed their views regarding solving any internal and external problems and direction from their administration as highly expected when they were in social security problem and stress. Conclusion: Study recommended that the gap between the internal, external social security systems of students and the reality should be assessed meticulously and to be addressed to achieve quality of medical education outcome. Bangladesh Journal of Medical Education Vol.14(2) July 2023: 10-17